Hawk tea prevents high-fat diet-induced obesity in mice by activating the AMPK/ACC/SREBP1c signaling pathways and regulating the gut microbiota. Issue 11 (19th April 2022) - Tao, Wei; Cao, Weiguo; Yu, Bao; Chen, Huan; Gong, Ruixue; Luorong, Quji; Luo, Juan; Yao, Ling; Zhang, Dan
Abstract : Hawk tea, a caffeine-free, non-Camellia tea, could attenuated weight gain, fat accumulation and lipid levels, and modify intestinal microbiota disorders, lipid metabolism. Abstract : Scope : Hawk tea, a non-Camellia tea, is an ancient tea drink from southwest China and has been proven to exhibit significant hypoglycaemic and lipid-lowering effects. The aim of this study was to evaluate whether Hawk tea extract (HTE) can improve obesity induced by a high-fat diet (HFD) in a mouse model and to determine whether its anti-obesity effects are related to improvements in lipid metabolism and the gut microbiota. Methods and results : We tested the ability of HTE to prevent obesity and regulate gut microbiota in C57BL/6J mice fed with a HFD. We found that HTE significantly reduced body weight, fat deposition, serum triglyceride (TG), total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels, and significantly increased serum levels of high-density lipoprotein cholesterol (HDL-C) induced by HFD. HTE also increased the levels of AMPK and ACC phosphorylation, up-regulated the expression of CPT-1, and downregulated the expression of SREBP1c and FAS. In addition, the administration of HTE significantly altered the composition of the gut microbiota, reduced the ratio of Firmicutes to Bacteroidetes, increased the relative abundance of Akkermansia muciniphila, Bacteroides-vulgatus, and Faecalibaculum_rodentium, and decreased the relative abundance of Desulfovibrionaceae and Lachnospiraceae . Conclusions : Collectively, our data demonstrate that HTE can prevent HFD-induced obesity by regulating the AMPK/ACC/SREBP1c signaling pathways and the gut microbiota.